Integration of Massage Therapy in Outpatient Cancer Care - Cowen, PhD, LMT, Virginia S.; Tafuto, MLS, Barbara (International Journal of Therapeutic Massage & Bodywork, 2018)
Background: Massage therapy can be helpful in alleviating cancer-related symptoms and cancer treatment-related symptoms. While surveys have noted that cancer patients seek out massage as a nonpharmacologic approach during cancer treatment, little is known about the integration of massage in outpatient cancer care. Purpose: The purpose of this study was to examine the extent to which massage is being integrated into outpatient cancer care at NCI-designated Cancer Centers. Setting: This study used descriptive methods to analyze the integration of massage in NCI-designated Cancer Centers providing clinical services to patients (n = 62). Design: Data were collected from 91.1% of the centers (n = 59) using content analysis and a telephone survey. A dataset was developed and coded for analysis. Main Outcome Measure: The integration of massage was assessed by an algorithm that was developed from a set of five variables: 1) acceptance of treatment as therapeutic, 2) institution offers treatment to patients, 3) clinical practice guidelines in place, 4) use of evidence-based resources to inform treatment, and 5) shared knowledge about treatment among health care team. All centers were scored against all five variables using a six-point scale, with all variables rated equally. Results: The integration of massage ranged from not at all (0) to very high (5) with all five levels of integration evident. Only 11 centers (17.7% of total) rated a very high level of integration; nearly one-third of the centers (n = 22) were found to have no integration of massage at all—not even provision of information about massage to patients through the center website. Conclusions: The findings of this analysis suggest that research on massage is not being leveraged to integrate massage into outpatient cancer care.